High-flow nasal cannula versus conventional oxygen therapy in patients with dyspnea and hypoxemia before hospitalization. (2nd April 2020) - Liu, Qi; Zhu, Changju; Lan, Chao; Chen, Rongchang
ABSTRACT: Introduction : Patients with dyspnea and hypoxemia are common in emergency departments. However, it is unknown whether high-flow nasal cannula (HFNC) reduces the risk of requiring more advanced ventilation support and whether HFNC relieves dyspnea better than conventional oxygen therapy (COT). Areas covered : We searched the PubMed, Cochrane Library, Ovid, and Embase databases from inception to 1 September 2019 to identify relevant-randomized controlled trials comparing the effect of HFNC with COT in emergency departments regarding the severity of dyspnea, hospitalization rate, intubation rate, and hospital mortality. We identified four studies. HFNC was associated with a lower rate of requiring more advanced ventilation. HFNC reduced the rate of dyspnea, lowered the dyspnea scale score, and decreased patients' respiratory rate significantly. However, there was insufficient evidence to show a significant effect on HFNC regarding patients' oxygenation and hospital mortality. Expert opinion : For patients with dyspnea and hypoxemia before hospitalization, the short-term effect of HFNC was undeniable. HFNC reduced the risk of requiring more advanced ventilation and relived dyspnea better than COT. HFNC might be considered as a first-line therapy even before making a clear diagnosis for dyspnea. More studies are needed to explore the effect of HFNC on oxygenation and patients' prognosis.